2004
DOI: 10.1074/jbc.m404097200
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Transcriptional Activation Is Mediated by Hypoxia-inducible Factor 1α, HDM2, and p70S6K1 in Response to Phosphatidylinositol 3-Kinase/AKT Signaling

Abstract: Vascular endothelial growth factor (VEGF) expression is elevated in ovarian and other cancer cells. However, the mechanism that causes the increase in VEGF expression still remains to be elucidated. In this study, we demonstrated that activation of PI3K signaling mediated VEGF protein expression at the transcriptional level through hypoxia-inducible factor 1␣ (HIF-1␣) expression in human ovarian cancer cells. We found that inhibition of PI3K activity by LY294002 decreased VEGF transcriptional activation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
153
3
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(168 citation statements)
references
References 32 publications
9
153
3
3
Order By: Relevance
“…However, little was known about the mechanism of FSH stimulation on VEGF expression. Other studies showed HIF-1α and survivin may play a role in VEGF expression [7][8][9][10][13][14][15][16], and it had also been shown that FSH induces HIF-1α and survivin expression [37][38][39]. In this study, we showed that treatment with FSH also increased survivin and HIF-1α expression (Figure 2A and 2B).…”
Section: Discussionsupporting
confidence: 66%
“…However, little was known about the mechanism of FSH stimulation on VEGF expression. Other studies showed HIF-1α and survivin may play a role in VEGF expression [7][8][9][10][13][14][15][16], and it had also been shown that FSH induces HIF-1α and survivin expression [37][38][39]. In this study, we showed that treatment with FSH also increased survivin and HIF-1α expression (Figure 2A and 2B).…”
Section: Discussionsupporting
confidence: 66%
“…S6K1 stimulates angiogenesis by increasing vascular endothelial growth factor (VEGF) production. Consistent with this, S6K1 overexpression reversed the LY294002-mediated inhibition of VEGF expression (Skinner et al, 2004). VEGF is essential for both physiological and pathological angiogenesis in cancer, such as ovarian cancers (Paley et al, 1997;Wang et al, 2006).…”
Section: S6kssupporting
confidence: 63%
“…VEGF is essential for both physiological and pathological angiogenesis in cancer, such as ovarian cancers (Paley et al, 1997;Wang et al, 2006). Activation of PI3K signaling mediates VEGF expression through the hypoxia-inducible factor 1a (HIF-1a) in human ovarian cancer cells (Skinner et al, 2004). Taken together, these data suggest an important role for S6K1 in coordinating key processes associated with tumor invasiveness and angiogenesis in ovarian cancer.…”
Section: S6ksmentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, Akt promotes cell growth by phosphorylation of the downstream mTOR complex 1 (mTORC1) [45] , which translates mRNAs to protein via the p70S6K-S6 and 4E-BP1-eIF4E pathways [46] . In addition, hypoxia-inducible factor 1α (HIF-1α) was reported to be upregulated downstream of mTORC1, and therefore promotes angiogenesis by transcribing VEGF (vascular endothelial growth factor) [47] . However, phosphorylation of S6K negatively regulates insulin receptor substrate (IRS) and PI3K, leading to a feedback loop [48][49][50] .…”
Section: Pi3k a Promising Molecular Target For Cancer Chemo Therapymentioning
confidence: 99%